2007
DOI: 10.1002/lsm.20541
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐assisted end‐to‐end bioweld® anastomosis in an ovine model

Abstract: The BioWeld tube, an albumin-based exovascular stent, has been used for microsurgical anastomoses and compared to conventional sutures. The study presented investigated the potential of the BioWeld tube for vascular anastomosis in larger vessels. Laser-assisted BioWeld anastomoses were compared to conventional-sutured anatomoses of the carotid artery of Merino-x ewes. The BioWeld procedure resulted in 100% survival and 100% patency at 1 and 6 week post-operative periods, with no noticeable foreign body respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Modification of the solid solder in the form of a BioWeld ring produced intact sutureless end-to-end anastomoses. However, the rigidity of the solder resulted in changes of vascular compliance [90].…”
Section: Figurementioning
confidence: 99%
“…Modification of the solid solder in the form of a BioWeld ring produced intact sutureless end-to-end anastomoses. However, the rigidity of the solder resulted in changes of vascular compliance [90].…”
Section: Figurementioning
confidence: 99%
“…Recent research has evaluated the ability of chemical materials, such as glues and/or dyes, to increase laser absorption and thus improve tissue welding strength . Most in vivo studies have used stay sutures , to approximate both edges of vessel segments and to increase tension.…”
Section: Introductionmentioning
confidence: 99%
“…A review paper published in 2004 identified 37 relevant studies of LAVA/LAVR , and we found additional 31 relevant studies published mainly after 2004 . Of these 68 studies, 26 evaluated LAVA/LAVR without stay sutures . In three of these studies, the edges of both vessel segments were approximated in an over‐wrapped manner using ring type joints or a catheter as core shaft .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation